Aluminium metal matrix composite: improving wear performance through treatment - Maleque, Md. Abdul; Karim, Md. Rezaul; Yassin, N. (Trans Tech Publications, Switzerland, 2011)
The main objectives of the present study are to develop/manufacture SiC reinforced aluminium matrix composite (SiCp/AMC) with different reinforcement combinations using stir casting method and investigate the effects of heat treatment on wear performance. AMCs were prepared using 20 vol% SiC with three different reinforcement combinations into aluminum matrix. Stir casting is a primary process of composite production whereby the reinforcement ingredient material is incorporated into the molten metal by stirring. The reinforcement combination consists of 20% (single particle size), 7% and 13% (double particle size) and 5%, 5% and 10% (triple particle size). The triple particle size (TPS) composite consist of SiC of three different sizes viz., coarse, intermediate and fine. The solution heat treatment was carried out on cast specimens at 540 °C for four hours followed by precipitation treatment. The wear test was carried out using a pin-on- disc type tribo-test machine under dry sliding condition. The wear morphology of the damaged surface was also studied using optical microscope and scanning electron microscope (SEM) in this investigation.